011 Role of coronary computed tomography angiography (CTA) in chest pain evaluation in females. (5th May 2016) - Shiwani, Hunain; Saunderson, Christopher; Anwar, Mohammed Mannan; Kon, Mark; Bulugahapitiya, Sudantha
Abstract : Introduction: Coronary computed tomography angiography (CTA) has a high negative predictive value for excluding significant coronary artery disease (CAD) with those with <50% luminal stenosis not requiring further investigation. Those with >50% stenoses require further non-invasive or invasive evaluation. Current NICE guidelines recommend CT calcium scoring as first-line investigation in patients with chest pain and an estimated likelihood of CAD of 10–29%. In females this includes those under 65 at low risk with atypical angina. The aim of this study was to evaluate coronary CTA as a single imaging modality to rule out significant CAD in females. Methods: We retrospectively assessed the coronary CTA findings of all female patients presenting with chest pain and undergoing assessment for possible underlying CAD at Bradford Royal Infirmary from January 2013 to December 2014. Patients were grouped according to age and this was assessed against the presence or absence of significant atheroma (>50% luminal stenosis). Results: 462 female patients underwent Coronary CTA with a median age of 57 (range 31–82). Coronary CTA was able to rule out significant CAD in a high proportion of all age ranges but became less sensitive with advancing age. Those with a stenosis of greater than 50% required further evaluation. Exclusion of significant CAD varied from 90% for females aged 30–49 to 87% in those aged 50–69 and remained as high as 78% for those over 70. Conclusion: Coronary CTA provides an effective single modality evaluation for chest pain in females including those over 65 years of age.